APPLICATION OF COSO PRINCIPLES AT PT SREEYA SEWU INDONESIA TBK - Darmawan, Ni Kadek Vidiasari; Banjarnahor, Erliana (Jurnal Magister Akuntansi Trisakti, 2025)
This study aims to analyze the implementation of COSO 2013 principles in the internal control system for raw material inventory at PT Sreeya Sewu Indonesia Tbk. The research employs a descriptive qualitative approach, collecting data through interviews, observations, document analysis, and a review of the 2023 annual report. The findings reveal that several COSO components, namely control environment, information and communication, and monitoring, have been consistently applied. However, weaknesses remain in risk assessment and control activities, particularly due to the inconsistent use of technology and limited integration across departments. These gaps reduce the overall effectiveness of the internal control system. The study emphasizes the need for stronger information system integration, standardized documentation of internal controls, and alignment of procedures across units. This research contributes to the literature on internal control in emerging markets, providing practical recommendations for enhancing governance and accountability in manufacturing companies.